Results report on a stakeholder workshop reflecting on a theory of change for low-emission food system transformation in Nandi county, Kenya: A contribution to the establishment of A Living Lab 4 People on Food System Innovations for Climate Change Mitigation under the CGIAR Research Initiative on Low-Emission Food Systems (MITIGATE+) - Falk, Thomas; Kibet, Walter (International Food Policy Research Institute, 2023)
The workshop was organized by the CGIAR Research Initiative on Low-Emission Food Systems (MITIGATE+), which is implemented by a large consortium of partners. The Initiative aims to reduce annual global food systems emissions by working closely with key actors in target countries to co-create knowledge that enables them to make evidence-based decisions and address challenges in food systems discourse, policy development, and implementation to reduce greenhouse gas emissions. The Initiative’s partners support the establishment of a multistakeholder platform and a “living lab for people” (LL4P) that will support bottom-up innovation cases to help transform food systems in Nandi county, Kenya, while also reducing greenhouse gas emissions. The workshop was part of a series of stakeholder workshops that aims to help clarify development opportunities, the role of different actors in Nandi county, and their interests. The intention was to bring actors together, invite them to think about a joint vision for food systems in the county, and share perspectives on entry points for initiating system change.